Forgiveness and Reconciliation Processes in Dying Patients With Cancer. (March 2020) - Renz, M.; Bueche, D.; Reichmuth, O.; Schuett Mao, M.; Renz, U.; Siebenrock, R.; Strasser, F.
This article studies forgiveness and reconciliation (F/R) in patients with cancer. It focuses on the end of life, when family conflicts resurface and unfinished business challenges patients and causes spiritual distress. Forgiveness and reconciliation may intensify patient–family relationships and facilitate peace of mind and peaceful death. Existing forgiveness models and interventions focus on coping in life, yet no study has examined F/R processes until death. Our mixed-method exploratory study hypothesized that F/R processes occur in phases, repeatedly, and are spurred by approaching death. Three interdisciplinary units at a major Swiss hospital observed 50 dying patients with cancer experiencing severe conflicts with relatives, themselves, and/or with fate/God. Participant observation was combined with interpretative phenomenological analysis and descriptive statistical analysis. A semi-structured observation protocol was developed based on a 5-phase model. The protocol included space for notes (emotions, interventions, effects on dying processes). It was assessed by 20 professionals for 1 year. Analysis was supported by international interdisciplinary experts. We found that conflicts were complex and involved relational, biographical, and spiritual layers. In 62% of patients, F/R processes occurred repeatedly. Many patients died after finding F/R (22 within 48 hours). Patients indicated that imminent death, a mediating third party, acceptance, and experiences of hope motivated them to seek F/R. Although deep relationships may support F/R processes, our limited data on near-death experience/spiritual experiences restrict interpretation. Forgiveness and reconciliation processes oscillate between 5 phases: denial, crisis, experience of hope, decision, and finding F/R. Understanding F/R processes, empathy, hope, and a neutral third party may support patients in seeking forgiveness.